2006
DOI: 10.1590/s1517-83822006000400028
|View full text |Cite
|
Sign up to set email alerts
|

Essential oil of Lithraea molleoides (Vell.): chemical composition and antimicrobial activity

Abstract: Lithraea molleoides (Vell.) (Anacardiaceae) is a tree found in Brazil, Paraguay, Bolivia, Uruguay, Argentina and Chile. It is popularly used in the form of alcoholic extracts, decoctions and infusions for the treatment of cough, bronchitis, arthritis, diseases of the digestive system and as diuretic, tranquilizer, haemostatic and tonic agent. The objectives of this study were the extraction of the essential oil of the mature fruit, leaves and aerial parts of the plant and quantification of the yield thereof; t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
1
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 18 publications
2
1
0
3
Order By: Relevance
“…Tassou and Nychas [ 6 ] also observed a greater effect on Gram-positive organisms for the oil from P. lentiscus (Anacardiaceae). Similar results were observed by Shimizu et al [ 30 ] for the oils from fruits of Lithraea molleoides .…”
Section: Resultssupporting
confidence: 91%
“…Tassou and Nychas [ 6 ] also observed a greater effect on Gram-positive organisms for the oil from P. lentiscus (Anacardiaceae). Similar results were observed by Shimizu et al [ 30 ] for the oils from fruits of Lithraea molleoides .…”
Section: Resultssupporting
confidence: 91%
“…Flavonoids and tannins were also reported by Lawrence (1984), as quoted by Santos et al (2008), and Queires and Rodrigues (1998). Santos et al (2010b) identified α-pinene and sabinene, which have bactericidal activity, in the essential oil of S. terebinthifolius (Shimizu et al, 2006), plus bicyclogermacrene, which has larvicide potential (Santos et al, 2006). These results suggest that these metabolites have a role in defense against herbivores and pathogens, and defense-related metabolites are known to also have allelopathic properties.…”
Section: Compounds Seasonal Semideciduous Forest Lowland Ombrophiloussupporting
confidence: 58%
“…Possui também atividades antimicrobianas, antivirais, citotóxicas e imunomoduladoras (Shimizu et al, 2006).…”
Section: Lafoensia Pacariunclassified